Discoid lupus erythematosus solely involving the eyelids: case report and literature review. (17th February 2021) - Wang, Xia; Wang, Peng; Wang, Ming; Huang, Xian; Wang, Cuiyan; Qu, Xiaoying; Xu, Jialu; Lu, Yuan; Chai, Bao; Huang, Changzheng
Abstract: Background and Objective: The involvement of eyelids occurs in only 5–6% of patients with discoid lupus erythematosus (DLE), commonly with mucocutaneous lesions elsewhere. DLE solely involving the eyelids is relatively rare. This study aimed to describe the clinical features and treatments of all the reported cases of DLE with eyelid involvement as the only symptom. Methods: A systematic review was done of all the related literature published both in English and Chinese from May 1, 1984, to March 1, 2020. Only those cases of DLE solely involving eyelids were selected and summarized in two tables. Results: (i) DLE solely involving the eyelids is five times more likely to affect females than males. (ii) The majority of cases were presenting with unilateral eyelid involvement. Lower lids, especially both lower lids, were the most commonly affected locations. (iii) An erythematous plaque with scales is the most frequent manifestation. (iv) Approximately 22.9% of the cases had a positive antinuclear antibody (ANA) titer, and the speckled pattern was the most seen. For direct immunofluorescence (DIF), 94.4% of the performed cases showed positive results. (v) More than 85% of these cases showed an excellent response to treatment with oral antimalarials. Conclusion: Awareness of this atypical presentation is important to avoid underdiagnosis of DLE solely involving the eyelids. A biopsy for both routine histology and DIF is critical for establishing the diagnosis.